Cerebral Oxygenation Dynamics of the Prefrontal Cortex and Motor-Related Area During Cardiopulmonary Exercise Test: A Near-Infrared Spectroscopy Study - Kojima, Sho; Morishita, Shinichiro; Qin, Weixiang; Tsubaki, Atsuhiro (Advances in experimental medicine and biology, 2020)
Near-infrared spectroscopy (NIRS) during cardiopulmonary exercise test (CPX) has shown a correlation between prefrontal cortex (PFC) oxygenated hemoglobin (O2Hb) level and negative affective responses. We hypothesized that O2Hb changes differ between the PFC and motor-related areas. This study investigated changes in hemoglobin levels in the PFC and motor-related areas during CPX. Twelve young healthy adults participated in this study. They performed a CPX after 4 min of rest and 4 min of warming up. Cortical O2Hb, deoxygenated hemoglobin (HHb), and total hemoglobin (THb) levels were measured with NIRS during CPX. Regions of interest (ROI) were the PFC, premotor area (PMA), supplementary motor area (SMA), and primary motor cortex (M1). The anaerobic threshold (AT), respiratory compensation (RC), and peak oxygen uptake (Peak) points were determined. The rest, AT, RC and Peak points of O2Hb, HHb, and THb were averaged over 5 s; hemoglobin slopes, from RC to the Peak points, were calculated to compare functional changes in cortical oxygenation. Average values of O2Hb, HHb, and THb in each ROI were compared among the rest, AT, RC, and Peak points. Average values of hemoglobin slopes, from RC to Peak points, were compared among ROIs using Bonferroni multiple comparisons. The HHb of all ROIs significantly increased at Peak point, compared with at the AT point. THb of the PFC, PMA, and SMA significantly increased at the RC or Peak points, compared with at the rest point. Hemoglobin slopes, from RC to Peak, showed no significant differences among ROIs. Each ROI exhibited similar changes, regardless of cortical function.